Respuesta :
In this item, we have:
A = 6x² + x +3
h = 3x
where ''A'' is area and ''h'' is height. From the statement above,
length of base, b = A / h
b = (6x² + x + 3)/3x
Thus, the expression for the length of the base is 6x²+x+3 / 3x.
A = 6x² + x +3
h = 3x
where ''A'' is area and ''h'' is height. From the statement above,
length of base, b = A / h
b = (6x² + x + 3)/3x
Thus, the expression for the length of the base is 6x²+x+3 / 3x.
Answer:
[tex]2x+\frac{1}{3}+\frac{1}{x}=Base[/tex]
Step-by-step explanation:
Given: The area of the parallelogram is [tex]6x^2+x+3[/tex] and the height is 3x.
To find: The base of the given parallelogram.
Solution: It is given that The area of the parallelogram is [tex]6x^2+x+3[/tex] and the height is 3x.
Now, area of parallelogram is given as:
[tex]A=b{\times}h[/tex] where b is the base and h is the height of teh gievn parallelogram.
Substituting the given values, we have
[tex]6x^2+x+3=b{\times}3x[/tex]
⇒[tex]\frac{6x^2+x+3}{3x}=Base[/tex]
⇒[tex]\frac{6x^2}{3x}+\frac{x}{3x}+\frac{3}{3x}=Base[/tex]
⇒[tex]2x+\frac{1}{3}+\frac{1}{x}=Base[/tex]
which is the required expression for the base of the given parallelogram.